2014
DOI: 10.2337/dc14-0005
|View full text |Cite
|
Sign up to set email alerts
|

Unnatural Deaths in a National Cohort of People Diagnosed With Diabetes

Abstract: OBJECTIVETo examine risk of unnatural death among people diagnosed with diabetes irrespective of disease type. RESEARCH DESIGN AND METHODSWe conducted a matched cohort study of the entire Swedish population using interlinked national registers. From the National Diabetes Register we identified 252,191 people diagnosed with diabetes (type 1 or 2) during 1996-2009. Each cohort member was matched for age, sex, and county of birth to five unaffected individuals randomly sampled from the Total Population Register. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 36 publications
2
12
0
Order By: Relevance
“…One study observed that the magnitude of suicidal behaviour in patients with type 2 diabetes was higher than the two-fold observed in the Mexican population (11.6% in patients with diabetes versus 5.2% in the general population) (33). The results were similar to previous reports showing that diabetes increases the risk of death by suicide (34,35). It was found that suicide attempters with T2DM showed higher levels of blood glucose than those without a history of suicide.…”
Section: Introductionsupporting
confidence: 91%
“…One study observed that the magnitude of suicidal behaviour in patients with type 2 diabetes was higher than the two-fold observed in the Mexican population (11.6% in patients with diabetes versus 5.2% in the general population) (33). The results were similar to previous reports showing that diabetes increases the risk of death by suicide (34,35). It was found that suicide attempters with T2DM showed higher levels of blood glucose than those without a history of suicide.…”
Section: Introductionsupporting
confidence: 91%
“…Intentional overdoses of insulin may underlie acute admissions for severe hypoglycemia of 'unknown' etiology, and this may also lead to the underestimation of suicide as a cause of death among patients with diabetes (20). However, the majority of suicides among the diabetic subjects in this study were attributable to psychotrophic drugs, as in the Swedish study (6) in which the use of insulin or hypoglycemic agents was identified as contributing to suicide in nine per cent of the cases. Nevertheless, according to the above-mentioned metaanalysis (5), the incidence ratio of suicide among diabetics was 2.85 per 10 000 person-years, on the basis of which it is estimated that globally there are about 94 000 suicides each year among diabetic individuals.…”
Section: Discussionmentioning
confidence: 58%
“…We identified self-harm from primary care records using clinician-verified Read codes [15] and from HES using the following ICD-10 codes: X60-84, Y87.0 and Y87.2. We used these same codes to identify suicide from ONS mortality data, with the addition of Y10-34 (excluding Y33.9) [16]. These codes represent undetermined intent, which is included in the ONS definition of suicide [17].…”
Section: Discussionmentioning
confidence: 99%